Training on Creating Instructional Videos on the History of Islamic Figures Using Google Flow for the Administrators of Nurul Huda Islamic Boarding School - Adib' Aunillah Fasya; Imam Prayogo Pujiono; Yunita Lisnaningtyas Utami; Arditya Prayogi; M. Wildan Ahfadh (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2026)
Digital transformation in education requires Islamic educational institutions to develop learning media that are more visual, adaptive, and aligned with the learning habits of digital natives. At Pondok Pesantren Nurul Huda Pandansari, the delivery of historical materials on Islamic figures is still dominated by verbal explanation and text-based learning resources, while the pesantren administrators have limited skills in using artificial intelligence tools to produce instructional videos. This community service activity aimed to improve the knowledge and skills of the administrators in creating instructional videos on the history of Islamic figures using Google Flow. The activity was conducted on 2 April 2026 at the computer laboratory of Pondok Pesantren Nurul Huda Pandansari and involved 8 participants. The methods used were presentation, practicum, and discussion. Program effectiveness was measured by comparing pre-test and post-test results consisting of five indicators of knowledge and practical competence. The results showed that the average achievement increased from 22.5% in the pre-test to 90.0% in the post-test. In addition, six participants successfully produced instructional videos of 1-2 minutes, while two participants completed storyboards and scene drafts ready for refinement. These findings indicate that practice-based training effectively strengthens digital literacy and learning-media production skills in the pesantren environment. Follow-up activities are recommended in the form of content production mentoring, thematic prompt banks, and the integration of the produced videos into Islamic history learning.